Design of standard CMOS time-of-flight pixel using charge transfer efficiency method - Din, Amad Ud (2011)
Time of Flight (TOF) range imaging is performed by sensing the delay time, TD of a known modulated light signal to reach the sensor after it has been back reflected from objects in a scene. This delay time is then used to measure distance of objects in a scene in real time. Recently, research on TOF image sensors has been receiving a great deal of attention mainly due to demand from scientific, medicine and industrial community. A CMOS TOF Pixels using the Gates on Field Oxide Structure has been realized where delay time dependant charge separation is achieved using two polysilicon gates that connect the photo collection site to two floating diffusion output nodes. The two outputs are consequently used to calculate the range of objects in a scene in real time. However, an extra mask layer is required to form a lightly doped n-buried layer under the gates and photo collection site to allow efficient charge transfer. Addition of this layer into the fabrication process increases cost. A solution to this is to design the pixel using standard CMOS circuit components. This thesis discusses the design of an Active Pixel TOF Sensor using high gain amplifiers to mimic the delay dependent signal charge separation mechanism as in the Gates on Field Oxide pixel. It focuses on amplifier selection based on its Charge Transfer Efficiency (CTE) which is defined as the ability of an amplifier to transfer charge from its input node to its output. Linearity of the TOF active pixel sensor depends on the CTE. Keeping in view the requirement of very high gain, four different types of amplifiers which are the Two-Stage OPAMP, Folded Cascode, Telescopic and Cascode amplifiers are designed using a 0.18μm CMOS process and analysed. From the analysis, it is concluded that the Cascode amplifier is best suited to be used in the TOF pixel as it has the highest gain of 131.21dB. This high gain gives a CTE of 95% while dissipating only1.32μW of power. The simulation concludes that a TOF pixel with a high CTE can be fabricated using an unmodified standard CMOS process, hence further reducing fabrication cost of these sensors.